Giant Cutaneous Leiomyoma of Scalp - Raj, Sumit; Joshi, Deepti; Agrawal, Amit; Mishra, Rakesh; Shrivastav, Adesh; Chouksey, Pradeep; Saha, Kaustav (Indian Journal of Neurosurgery, 2024)
Leiomyomas are benign tumors arising from smooth muscle, most commonly seen in uterine myometrium, gastrointestinal tract, skin, and lower extremities of middle-aged women. Leiomyomas of head and neck region account for less than 1% of all leiomyomas. The most common site of leiomyoma in the head and neck region is the lips followed by tongue, and other maxillofacial regions. The clinical features, etiology, differential diagnosis, and treatment of leiomyoma are discussed in this case report. The aim of this case report is to raise awareness about a rare form of scalp giant leiomyoma. This could expand its consideration as a possible cause of uncertain neoplasms and promote accurate clinical diagnosis, leading to better treatment results.
Keywords: giant leiomyoma; neurosurgery; scalp leiomyoma